THE INFLUENCE OF PHYSICAL FITNESS LEVEL IN BODY IMAGE OF TEENAGERS (Fiep Bulletin - online, 2013)
The aim of this study was to evaluate and quantify the level of physical fitness of adolescents and how it influences the body image of themselves. This is a descriptive research with quantitative approach. The sample consisted of 52 adolescents attending 2nd year of high school at a public school in Fortaleza, CE (Brazil), aged between 15 and 18 years. The instruments used to collect data were: a battery of tests of engines which is composed of tests that assess: aerobic fitness, body composition, muscular strength and endurance and flexibility, and the Brazilian version of  “Escala de Evaluación de Insatisfación Corporal para Adolescentes - EEICA”. All questions were statistically computed using SPSS version 19. The study revealed that the average total score is 20.5 EEICA with a minimum of 3 and a maximum of 86. In boys the mean value was 12.9 and in girls from 26.5. It can be concluded that, predominantly, teens are satisfied with their body image. Fact that can be observed both in the low value of the mean frequency values ??as in regarding the response "never", which was prevalent in 18 of the 25 questions in the positive direction. That is, they never are dissatisfied with their body image, according to those issues of scale that can be a result of the classification of 78.9% as eutrophic by BMI. It is noteworthy that the highest scores were presented in females, which did not give any satisfactory test of aerobic endurance, and when combined with the results of skin folds, stands out with 10.5% risk for developing cardiovascular disease. In short, teens are satisfied with their body image, but the higher frequency of dissatisfaction comes from females.
Keywords: Physical Education; Teenagers; Physical Fitness; Body Image